Differences between Slovak and Dutch patients scheduled for coronary artery bypass graft surgery regarding clinical and psychosocial predictors of physical and mental health-related quality of life. (1st April 2018) - El-Baz, Noha; Ondusova, Daniela; Studencan, Martin; Rosenberger, Jaroslav; Reijneveld, Sijmen A; van Dijk, Jitse P; Middel, Berrie
Abstract: Background: Differences in health-related quality of life in coronary artery disease patients and associated factors between patients of central and western European descent are rarely investigated. We aim to test differences between Dutch and Slovak health-related quality of life, whether nationality predicted health-related quality of life and if standardised beta weights of health-related quality of life determinants differ across countries. Design: An observational multicentre study at university cardiac centres in the Netherlands and Slovakia. Methods: In 226 coronary artery disease patients, health-related quality of life was measured by the Short Form Health Survey 36, anxiety and depression were measured using the Hospital Anxiety and Depression Scale, and type D personality was assessed with the 14-item Type D Scale. Multivariate analysis was used to explore the effect of patient characteristics on the physical and mental component summaries. Estimates of each predictor's beta value of the physical and mental component summaries in the Slovak and Dutch patient sample were separately calculated using the Cummings criterion for comparison of two independent betas. Results: Stronger predictors of physical health-related quality of life in Slovak patients were educational level, current smoking, poor functional status, history of diabetes and amount of social support. In Dutch patients, only more symptoms of depression was a stronger predictor ( P <0.05). Regarding Slovak mental health-related quality of life, stronger predictors were educational level, current smoking and amount of social support. Female gender, history of myocardial infarction and more symptoms of depression were stronger predictors in Dutch patients ( P <0.05). Conclusion: Descent and differences between both populations in determinants of health-related quality of life should be considered while planning care, follow-up, health education and rehabilitation.